Evaluation and training of basic and initial techniques for probing cane use in school environments - Orbolato, Loiane Maria Zengo [UNESP]; Manzini, Eduardo José [UNESP] (FapUNIFESP (SciELO), 2020)
The aim of this study was to evaluate a program for training basic probing cane techniques in the school environment. A 13-year-old female student with congenital blindness enrolled in the 1st grade of Middle School participated in the study. The instruments used were the evaluation protocols of the basic orientation and mobility techniques. The evaluation took place in three environments: corridors, classroom and schoolyard, and the quasi-experimental design consisted of pretest, intervention and posttest. The analysis was quantitative for the student’s performance and, in the intervention, it was qualitative for the choice of the teaching strategies. The results of the pretest indicated that the student had no difficulty in performing the basic behaviors of the proposed techniques, but failed to perform those that are specific, which were the focus of the training. The teaching strategies were explanations, instructions and presentation of kinesthetic models. Posttest results pointed out that the student was able to perform most behaviors of all techniques in all environments. It was concluded that the training program was successful due to: the quasi-experimental study type that objectively allowed the evaluation of behaviors; registration and filming forms, which ensured control of the teaching process; the teaching strategies employed; teaching and training focused on the blind student’s natural environment. Two points were identified as necessary to improve the use of the techniques: the type of clothing, the accessories, the student’s shoes and the training time.
Avaliação e treinamento das técnicas básicas e iniciais para a locomoção com a bengala em ambientes escolares
Keywords: Orientation and Mobility; Probing Cane; Special Education; Training